Engineering properties of older alluvium - Hamood Alshameri, Badee Abdulqawi (2010)
Moisture content is one of the most crucial factors influencing soil and rock strength. This paper deals with the effect of moisture content on strength of older alluvium under dry, wet and saturated conditions. Older alluvium is semi cemented eroded deposited and reshaped by water to make non-marine setting. Specimens were tested in for shear strength, hardness and point load index. According to these results, the petrophysical properties of older alluvium decrease with increasing moisture. The strength was extremely reduced after the moisture content increased over the range of natural moisture content i.e. at saturated condition. For soil mechanics and soil engineering projects the shear strength, friction angle and cohesion assess at dry condition in order to give classification for soil strength. While the design parameters (shear strength, friction angle and cohesion) were taken at weak condition i.e. saturated and wet condition. However the difficulties and non reliable preparing regular samples at laboratory, most of samples destroyed during the sample preparation. Point load apparatus and Schmidt (rebound) hammer test did not able to record any reading during test the samples for both wet and dry condition. Older alluvium shows equilibrium between distribution of the clay/silt and gravel with percent finer approximately 38% and 38.5% respectively, and lower presence of sand with percent finer approximately 23.4%. The range of natural moisture content was within range of 17.98 to 19.65%. The results revealed that moisture content have great influence in the reduction of the shear strength t, friction angle Ø and cohesion c. When the moisture content on older alluvium deposits increased the shear strength reduced to 22.3% and to 75.3% at wet and saturated condition respectively (the shear strength equal to 57.4kPa and 18.3kPa for wet and saturated condition respectively) in comparison to the magnitude of shear strength at dry condition (shear strength at dry condition equal to 74.1kPa). The same as for friction angle, when the moisture content increased the friction angle reduced to 18.6% and 66.9% at wet condition and saturated condition respectively (friction angle equal to 55.19o and 22.45o for wet and saturated condition respectively) in comparison to the magnitude at dry condition (at dry condition friction angle equal to 67.83o). Otherwise the effective of increase the moisture content at cohesion is different i. e. the magnitude of cohesion at dry condition was equal to 21.044 kPa. At wet condition the cohesion increased to 12.7% (cohesion equal to 23.71kPa) in comparison to the magnitude at dry condition. At saturated condition the cohesion value will decreased to 54.6% (cohesion equal to 9.54 kPa) in comparison to the magnitude at dry condition.